The Metaphor of Craving in the Tanha Vagga of the Dhammapada Scripture (Semantic Study of Buddhist Texts) - Santi Paramita; Hesti Sadtyadi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
The purpose of this study is to describe: (1) Haley’s model of human perceptual space category used to create the metaphorical expression of craving in the Tanha Vagga verse of the Dhammapada scripture, (2) the distribution of Haley's category of human perceptual space that is most prominently used to create the metaphorical expression of craving in the Tanha Vagga verse of the Dhammapada scripture, (3) the state of the ecological system as seen in the metaphor of craving in the Tanha Vagga verse of the Dhammapada scripture based on the distribution of the use of the Haley’s category of the human perceptual space. This research is a descriptive-qualitative research, with Content Analysis technique. The data source is the Tanha Vagga Dhammapada Scripture. The results showed: (1) in the Tanha Vagga scripture Dhammapada there are 31 metaphors of craving that can be categorized into the five spaces of human perception according to Haley's model, including the categories of being, energy, terrestrial, object and living. (2) Based on the results of the distribution of the use of the Haley’s model of human perceptual space, it was found that the living category was the most prominent type of craving metaphor category with a percentage of 35.4%, (3) the percentage distribution results reflected the unbalanced state of the ecological system in the Tanha Vagga verses of Dhammapada. The metaphorical expression of craving in the Tanha Vagga of the Dhamapada scriptures is packaged in a metaphorical form which means controlling lust (taṇhā = Pali) which causes dukkha (suffering) and the cycle of rebirth (saṃsāra). Buddhism seeks to eliminate taṇhā to eliminate dukkha.